Does Expanding Access to Cannabis Affect Traffic Crashes? County-Level Evidence from Recreational Marijuana Dispensary Sales in Colorado - Christian Gunadi (Global Labor Organization (GLO), 2021)
This article examines the effect of recreational cannabis dispensary sales on traffic crashes by employing difference-in-differences model that exploits the variation in the timing of recreational marijuana dispensary entry across counties within Colorado. Using marijuana-related hospital discharge as a proxy for marijuana use, the results indicate a sizable rise in marijuana-related hospital discharges after the entry of retail cannabis stores. However, there is a lack of evidence that traffic crash incidents are affected by the entry. The preferred estimate suggests that, at 90% confidence level, a large increase in traffic crashes by more than 5% can be ruled out.
Keywords: K00; I1; R41; H23; 330; Recreational Marijuana Laws; Cannabis Access; Traffic Crashes